Colony-level sex ratio in the eusocial Hymenoptera - Boomsma, J; Grafen, A (1991)
A simple marginal value argument shows that "assessing' workers maximize their inclusive fitness by specializing on the production of the sex to which they are relatively more related than the average worker in the population is related to that sex. In large populations all but one of the relatedness-asymmetry classes should specialize on the production of one sex only. The remaining, balancing class is selected to compensate any bias induced by the other class(es) such that the population sex ratio reflects the relatedness asymmetry of that balancing class. In the absence of worker-reproduction, the sex ratio compensation by the balancing-class is generally close to 100%, unless the population is very small. -from Authors